Psoriasin: A Novel Marker Linked Obesity with Psoriasis. Issue 1 (21st May 2013) - Salama, Ragaa H. M.; Al-Shobaili, Hani A.; Al Robaee, Ahmad A.; Alzolibani, Abdullateef A.
Abstract : To evaluate the role of psoriasin, koebnerisin, interleukn (IL)-12 and IL-23 in the pathogenesis of psoriasis and their relations to Psoriasis Area Severity Index (PASI) and obesity. Thirty patients had chronic plaque psoriasis and 30 healthy subjects matched in age and sex were enrolled in this study. Serum from all subjects were used for determination of psoriasin, koebnerisin, IL-12 and IL-23 by ELISA kits. IL-23 and psoriasin were significantly higher in skin psoriasis compared to controls and psoriatic arthritis (PsA). There was a correlation between psoriasin and both PASI and obesity. On the other hand, IL-12 was significantly increased in PsA compared to skin psoriasis ( p = 0.000) and controls. Its sensitivity and specificity were 87%, 93%; respectively. To our knowledge, psoriasin is the first biomarker confirm the link between obesity and psoriasis. The risk of developing psoriasis is directly related to higher BMI.